please answer this question
![](https://hi-static.z-dn.net/files/db4/e2db8da723a044a438f330fba287460f.jpg)
Answers
Answer:
it is too much easy
Step-by-step explanation:
you you can do it by the algebra method of the maths
[tex]\mathfrak{\huge{Answer:-}} \\ \frac{14 {x}^{2} - 6x + 8}{10 {x}^{2} + 4x + 7 } = \frac{7x - 3}{5x + 2} \\ Cross \: multiply \\ (5x + 2)(14 {x}^{2} - 6x + 8) = (7x - 3)(10 {x}^{2} + 4x + 7) \\ 5x(14 {x}^{2} - 6x + 8) + 2(14 {x}^{2} - 6x + 8) = 7x(10 {x}^{2} + 4x + 7) - 3(10 {x}^{2} + 4x + 7) \\ 70 {x}^{3} - 30 {x}^{2} + 40x + 28 {x}^{2} - 12x + 16 = 70 {x}^{3} + 28 {x}^{2} + 49x - 30 {x}^{2} - 12x - 21 \\ 70 {x}^{3} - 70 {x}^{3} - 30 {x}^{2} +30 {x}^{2} + 28 {x}^{2} - 28 {x}^{2} + 40x - 12x - 49x + 12x + 16 + 21 = 0 \\ ( - 9x) + 37 = 0 \\ ( - 9x) = ( - 37) \\ 9x = 37 \\ \boxed{\boxed{\large{ x = \frac{37}{9} } }} [/tex]